ANALYSIS OF THE FAMILY SITUATION OF SCHOOLCHILDREN WITH MALADJUSTMENT (Medical science of Uzbekistan, 2024)
The emergence of deviant behavior in adolescents depended not so much on the material well-being, but on the negative climate. Low levels of education and culture of their parents, neglect, cruelty, parents, family fight, physical punishment, abuse of alcohol, create certain conditions to follow